Effect of fat replacer systems and maltitol on qualities of fat and calorie reduced dairy ice cream - Phianmongkhol,A. (Chiang Mai University, 2015)
This research aimed to study the effect fat replacer systems (single and mixed) and concentration of maltitol on physical, chemical and sensory properties of fat and calorie reduced dairy ice cream. In single fat replacer system, two protein-based fat replacers (i.e. whey protein and soy protein) were studied. Experimental results indicated that whey protein provided the ice cream of higher overrun value and lower meltdown rate as compared with those of soy protein. When mixed fat replacer system (protein-based and carbohydrate-based fat replacers) was used, results revealed that combination of whey protein and Avicel (4:1) (w/w) provided the ice cream with similar value of viscosity, protein content and sensory property to those of control sample (P > 0.05). However, the melting rate and fat content of the ice cream with the mixed fat replacer system were lower while the overrun was higher than the control (P ≤ 0.05). Properties of fat reduced ice cream (used mixture of whey protein: Avicel of 4:1 (w/w) as fat replacer) with 10 % (w/w) maltitol were similar to the control sample (P > 0.05). Based on this ice cream formula, the fat and energy content of the ice cream were measured to be 2.21±0.26 % and 448.97±2.94 kcal/100 g, respectively. The results form this study suggested that the mixed fat replacer system and maltitol had a potential to be used in the fat and calorie reduced ice cream product.